PENGARUH IKLIM ORGANISASI, PENDIDIKAN DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL (PNS) PADA KANTOR KECAMATAN BAHODOPI KABUPATEN MOROWALI - Arsan, Arsan (Katalogis, 2016)
The aims of this research are: 1) to determine and analyze simultaneous influence of organizational climate, education, and work culture on the performance of civil servants at The Bahodopi District Office; 2) to determine and analyze the influence of organizational climate on civil servants’ performance; 3) to determine and analyze the influence of education on civil servants’ performance; 4) to determine and analyze the influence of work culture on civil servants’ performance. Based on these aims, the research employs associative explanatory approach by involving 30 respondents who are selected with census method. The results of multiple linear regressions test show that: 1) organizational climate, education, and work culture simultaneously have positive and significant influence on the performance of civil servants at The Bahodopi District Office; 2) organizational climate has positive and significant influence on civil servants’ performance; 3) education has positive and significant influence on civil servants’ performance; 4) work culture has positive and significant influence on civil servants’ performance.